Comparison of biosimilar filgrastim, originator filgrastim, and lenograstim for autologous stem cell mobilization in patients with multiple myeloma - Kriegsmann, Katharina; Bärtsch, Marc-Andrea; Bruckner, Thomas; Kriegsmann, Mark; Schmitt, Anita; Witzens-Harig, Mathias; Ho, Anthony Dick; Hillengaß, Jens; Wuchter, Patrick (Transfusion, 2017)
Background: Granulocyte-colony-stimulating factor (G-CSF) originators such as filgrastim (Neupogen) and lenograstim (Granocyte) are widely used for peripheral blood stem cell (PBSC) mobilization. In recent years, biosimilar agents have been approved for the same indications. The aim of this retrospective study was to compare the mobilization efficiency of the three G-CSF variants originator filgrastim, lenograstim, and the biosimilar Filgrastim Hexal in a homogeneous group of multiple myeloma (MM) patients in first-line therapy. Study design and methods: Overall mobilization data of 250 patients with MM were included. Of these patients, 74 (30%), 131 (52%), and 45 (18%) were mobilized with originator filgrastim, biosimilar Filgrastim Hexal, or lenograstim, respectively, at a dose of 5 to 10 µg/kg body weight subcutaneously starting from Day 5 after chemomobilization with CAD (cyclophosphamide, doxorubicin, dexamethasone) until completion of PBSC collection. Results: All but one patient reached the collection goal of a minimum of at least 2 × 106 CD34+ cells/kg body weight during a median of one (range, one to three) leukapheresis session. No significant differences in CD34+ mobilization and collection yields between the filgrastim-mobilized (median, 10.5; range, 2.7-40.4), Filgrastim Hexal-mobilized (median, 9.9; range, 0.2-26.0), and lenograstim-mobilized (median, 10.7; range, 3.1-27.9 CD34+ cells × 106/kg body weight) patients were observed. Conclusion: Concerning the clinically relevant efficiencies of PBSC mobilization and in terms of reaching the individual collection target, this retrospective study did not detect any significant differences between the three G-CSF variants in the analyzed patient cohort.